Diagnostic challenges of focal nodular hyperplasia: interobserver variability, accuracy, and the utility of glutamine synthetase immunohistochemistry. Issue 5 (6th August 2021) - Rowan, Daniel J; Allende, Daniela S; Bellizzi, Andrew M; Gill, Ryan M; Liu, Xiuli; McKenzie, Catriona A; Moreira, Roger K; Mounajjed, Taofic; Said, Samar; Westerhoff, Maria; Jenkins, Sarah M; Batts, Kenneth P; et al.
Abstract : Aims: The diagnosis of focal nodular hyperplasia (FNH) and the interpretation of glutamine synthetase (GS) staining can be challenging on biopsies. We aimed to evaluate the reproducibility of needle biopsy diagnosis of FNH, the effect of GS immunohistochemistry on FNH diagnosis, and which histological features are most useful for the diagnosis of FNH. Methods and results: The study included virtual needle biopsies generated from 75 resection specimens (30 FNHs, 15 hepatocellular adenomas, 15 hepatocellular carcinomas, and 15 non‐lesional liver specimens). Pathologists were reasonably accurate (83.1%) in the diagnosis of FNH with haematoxylin and eosin alone. Ductular reaction and nodularity had the highest sensitivity for a diagnosis of FNH (88.1% and 82.2%, respectively), whereas central scar was the most specific feature (90.6%). The presence of two or more of the classic histological features had 89.6% sensitivity and 86.2% specificity for a diagnosis of FNH. Diagnostic accuracy was significantly higher with the addition of a GS stain. A map‐like GS staining pattern was highly specific (99.3%) for FNH. However, GS staining was interpreted as non‐map‐like in 14.4% of reviews of true FNH cases, and overall interobserver agreement for interpretation of the GS staining pattern was only moderate (kappa = 0.42). Conclusions: Pathologists are reasonably accurate in the diagnosis of FNH on virtual biopsies, and GS staining improves accuracy. However, a subset of FNH cases remain challenging. Steatosis and a pseudo‐map‐like GS staining pattern were associated with increased difficulty. Therefore, although a map‐like GS staining pattern is useful for confirmation of a diagnosis, the lack of a map‐like GS staining pattern on needle biopsy does not necessarily exclude a diagnosis of FNH. Abstract :